2016
DOI: 10.1128/jcm.00521-16
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Rapid Test for Diagnosis of Dengue during Suspected Dengue Outbreaks in Resource-Limited Regions

Abstract: G lobally, over 2.5 billion people are estimated to be at risk of dengue virus (DENV) infection with an estimated 96 million symptomatic cases of dengue occurring annually (1). Despite ongoing research efforts, there are no sustainable vector control approaches or effective antiviral drugs to prevent or treat dengue, and vaccines have only recently been licensed by few countries and with suboptimal efficacy (2, 3, 4, 5). However, improvements in patient clinical management has been shown to reduce mortality am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
(40 reference statements)
3
36
0
1
Order By: Relevance
“…Dengue RDTs are useful for identifying a dengue outbreak but are less useful in individual case management in clinical settings. The sensitivity and specificity of dengue RDTs are variable depending on factors including DENV serotype, date of collection, the skill of technician and history of previous DENV infections in individuals [ 54 ]. The lack of guideline for the appropriate use of dengue RDTs during an outbreak likely contribute to their inappropriate use and stock depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue RDTs are useful for identifying a dengue outbreak but are less useful in individual case management in clinical settings. The sensitivity and specificity of dengue RDTs are variable depending on factors including DENV serotype, date of collection, the skill of technician and history of previous DENV infections in individuals [ 54 ]. The lack of guideline for the appropriate use of dengue RDTs during an outbreak likely contribute to their inappropriate use and stock depletion.…”
Section: Discussionmentioning
confidence: 99%
“…23 Another study also showed that the highest IgM antibody positivity (83%) was detected on the 5 th day of fever. 24 Therefore for patients with 5-day fever, accompanied by signs and symptoms relevant with DENV infection, detection of IgM and IgG anti-DENV antibody should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is reported that the RDTs have different sensitivity and specificity in primary and secondary infection, Timing and storage of specimen, and to the infection by different serotypes . Another resent study that compared the RDT test with qRT‐PCR and reported that RDT was useful in limited resource areas.…”
Section: Discussionmentioning
confidence: 99%
“…These tests are economical and are easy to perform. Several studies have reported evaluation of RDTs, using different study designs and comparing the RDTs with ELISA, RT‐PCR, and qRT‐PCR in different conditions . But there are limited studies documenting DENV serotype specific evaluation of RDTs.…”
Section: Introductionmentioning
confidence: 99%